The role of Seladelpar in primary biliary cholangitis: a systematic review and meta-analysis - Taimoor Ashraf; Omar Abunada; Nandlal Seerani; Kashif Ali; Areej Muhammad; Syeda Lamiya Mir; Syed Adil Mir Shah; Muhammad Hassaan; Vikash Kumar; Waseem Abbas; Simran Bajaj; Asfia Qammar; et al. (BMC Gastroenterology)
Abstract Introduction Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease characterized by progressive bile duct destruction, leading to cholestasis and, if untreated, liver failure. Although ursodeoxycholic acid (UDCA) remains the first-line treatment, many patients exhibit an inadequate response, necessitating alternative therapeutic options. Seladelpar, a peroxisome proliferator-activated receptor delta (PPAR-δ) agonist, has emerged as a promising alternative due to its anti-inflammatory and anti-fibrotic properties. Methods A systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted to evaluate the efficacy and safety of Seladelpar in patients with PBC. A comprehensive database search was performed to identify studies comparing Seladelpar with placebo. Primary and secondary outcomes, including alkaline phosphatase (ALP) normalization, biochemical response, and adverse events, were analyzed. Results Three RCTs, comprising 496 patients, were included. Seladelpar significantly improved ALP normalization and biochemical response compared to placebo. Additionally, it effectively reduced ALP and ALT levels from baseline to follow-up. Adverse events, including abdominal pain and headache, were reported, with a higher incidence observed in the Seladelpar group, while other adverse events showed no significant differences between groups. Conclusion Seladelpar appears to be an effective treatment for PBC, demonstrating significant improvements in key liver function markers. While it has shown therapeutic benefits, further research is warranted to evaluate its long-term safety, particularly regarding adverse event incidence, and to determine its efficacy across different dosages.